Postprandial oxidative stress: Influence of sex and exercise training status - Bloomer, R. J.; Ferebee, D. E.; Fisher-Wellman, K. H.; Quindry, J. C.; Schilling, B. K. (Medicine & Science in Sports & Exercise, 2009)
An individual's sex and exercise training status may influence oxidative stress. No study has compared postprandial oxidative stress in exercise-trained and untrained men and women.